An Addition to the Grace and Holy Trinity Cathedral, Kansas City, Missouri - Abend Singleton Associates Incorporated (Oz, 1982)
Grace and Holy Trinity Cathedral is comprised of parts erected over the past century. The sanctuary was built between 1887-1890, its tower added in 1893-1894, according to a new design. The Guild Hall was constructed in 1938, the school building in the 1950's…